"Splitting the bill" for conservation: Perceptions and uptake of financial incentives by landholders managing privately protected areas. Issue 4 (22nd February 2022) - Selinske, Matthew J.; Howard, Natasha; Fitzsimons, James A.; Hardy, Mathew J.; Knight, Andrew T.
Abstract: Globally, privately protected area (PPA) programs are increasing in size and number. Participating in a PPA program can be fiscally challenging for landholders (e.g., enrollment costs; potential reduction in land value; opportunity costs; costs of ongoing management). Government and nongovernmental organizations often offer financial incentives to landholders, in addition to nonfinancial incentives, to encourage program enrollment and ongoing biodiversity management. In Australia, where conservation covenanting programs have been ongoing for several decades, a diversity of financial incentives is available to landholders. We surveyed 527 conservation covenantors from three states in southeast Australia to investigate the uptake, use, experience and preference for financial incentives. Less than half of covenantors received a financial incentive to enroll, but most applied for some form of incentive after enrollment, predominantly to help with management costs. Covenantors identified challenges in accessing incentives, such as being unaware of funding opportunities or experiencing confusing application processes. We found land rates rebates to be the preferred financial incentive among covenantors, in part due to the perception that covenantors should not have to pay full rates on covenanted land. Our results suggest that while covenantors do not participate in PPA programs for financial incentives, effectively and efficiently deploying financial incentives can reduce the financial burdens of PPA management, potentially increasing the effectiveness of conservation efforts.